Tata Ruang Rumah Ideal dalam Novel Teka-Teki Rumah Aneh Karya Uketsu - Ifroh Ya Albi; Muhammad Raaid Hammas El Ghazali; Eva Dwi Kurniawan (Indonesian Journal Publisher, 2024)
Houses, serving as spaces for human interaction and socialization, require meticulous design to create environments that provide protection and comfort. This research focuses on spatial layout within homes as a critical factor influencing functionality, aesthetics, and inhabitant health, referencing Uketsu's novel